A Cost-Optimized Model for Dynamic Port Hinterland Delineation: An Application to the Spanish Port System - Manuel Francisco Martínez Torres; Juan Jesús Ruiz Aguilar; Ignacio J. Turias Domínguez; María del Mar Cerbán Jiménez (Applied Sciences)
This study presents a methodology for determining port economic hinterlands through comprehensive logistics optimization. The research advances traditional geographical approaches by developing an integrated cost model that considers maritime transport, inland transportation, warehousing expenses, and time-dependent factors. Testing this methodology on the Spanish port system (with three main ports: Valencia, Algeciras, and Barcelona), we demonstrate how product characteristics and origins significantly influence optimal port selection and hinterland boundaries. The analysis examines both perishable goods, using bananas and oranges as case studies, and non-perishable cargo from Asian and American origins. Results reveal distinct patterns of port influence depending on goods type and origin. The study’s findings, visualized through innovative color-coded mapping, provide valuable insights for port authorities and logistics planners in optimizing supply chain decisions. Our approach contributes to port competition theory by establishing a quantitative framework for dynamic hinterland delineation based on actual logistics costs and operational factors.